EU Environmental Protection in Regard to Sustainable Development: Myth or Reality? - Ivana Špelić; Alka Mihelić-Bogdanić (Standards)
According to conclusions agreed to in the 1995 Report of the World Summit for Social Development and the 2015 Sustainable Development Summit, seventeen sustainable development goals (SDGs) have been ratified and published as the 2030 Agenda for Sustainable Development. In 2022, the 8th Environment Action Programme was legally agreed upon, following the six European Green Deal priorities. These SDGs serve as a constant reminder of the importance of globally coordinated actions in compliance with the theory of sustainable development. However, more than a constant reminder, this international agreement should become the foundation for necessary change. On 22 July 2024, the daily global average temperature reached a new record high. The EU treaties signed between 1951 and 2007 laid the foundation for the creation of EU environmental policy. However, those EU treaties, along with environmental policy, form merely a non-binding and minimum set of priorities without any sanctions imposed for illegal practices. In 2021, EU member countries adopted the European Climate Law as the first legally binding document seeking to achieve goals set by the Paris Agreement and the European Green Deal. Any further EU sustainable development policies are dependent on global cooperation as a key element of survival. With the EU’s dependent on the rest of the world for its energy, the forcing of any obligatory change will be hard to achieve. This proves the importance of the 17th SDG, agreed in 2015. Only global partnership for sustainable development can prevent further damage to our ecosystem and achieve priorities set by the EU and UN agendas. The review aims to present the connection between sustainable development (SD) goals defined by the European Commission, for which the most important aspects are the need to meet the environmental requirements to protect future needs in the long run, and to confront the shortcomings of European law-making practices, in which most crucial reforms are presented as non-binding legal acts. Finally, in 2024 members of the European Parliament established an extended list of environmental crimes to be regarded as punishable offences and replaced the Environmental Crime Directive, making criminal activities and offences potentially legally punishable; however, it is yet to be seen how this initiative will be incorporated within the national legislations of each EU member country and to what extent.